A CALL FOR A DIFFERENCE IN TREATMENT BETWEEN CHILD AND ADULT OFFENDERS IN THE SOUTH AFRICAN PAROLE SYSTEM: AN INTERNATIONAL LAW PERSPECTIVE (The Pretoria Student Law Review, 2021)
Internationally, parole is recognised and accepted as a means of the conditional release of a sentenced offender from a correctional centre into the community, before the expiration of the judicially imposed sentence of such offender.  The functions of the placement on parole of the offender, which associate with the offender, include the rehabilitation of the offender and his reintegration into the community, as well as his restitution (e.g. in the form of symbolic restitution or community service). In Correctional Services authorities, parole acts occur to relieve prison overcrowding, encourage good behaviour within correctional facilities and to save costs related to imprisonment without negating the benefits of continued supervision and control.5 In South Africa, parole is predominantly governed by the Correctional Services Act 111 of 1998 (as amended) or, more particularly chapter IV (dealing with sentenced offenders), chapter VI (community corrections) and chapter VII (release from correctional centre and placement under correctional supervision and on day parole and parole). The provisions of chapter IV came into operation on 31 July 2004, whilst those of chapters V and VI came into operation on 1 October 2004.6 In addition, the provisions of the Correctional Services B-Order, Sub-Order 1, Incarceration Administration (hereinafter referred to as the Parole Manual) go a long way in clarifying and expanding on provisions in the Correctional Services Act, as well as indicating the practice and policy of the various functionaries involved in the parole system. Section 28(1)(g) of the Constitution of the Republic of South Africa, 1996 (Constitution), on the other hand, provides that a child has the right not to be detained except as a measure of last resort and then only for the shortest appropriate period. Section 28(2) further provides that a child’s best interests are of paramount importance in every matter concerning the child. The question can then be raised: what effect do the above provisions have on the parole consideration of child offenders? Additionally, one can ask whether there is sufficient justification for a difference in parole treatment between child and adult offenders.
Keywords: parole; rehabilitation of the offender; Correctional Services Act; child offenders; child’s best interests